Extensive Differences in Antifungal Immune Response in Two Drosophila Species Revealed by Comparative Transcriptome Analysis - Yosuke Seto; Koichiro Tamura (International Journal of Genomics)
The innate immune system of Drosophila is activated by ingestion of microorganisms. D. melanogaster breeds on fruits fermented by Saccharomyces cerevisiae, whereas D. virilis breeds on slime flux and decaying bark of tree housing a variety of bacteria, yeasts, and molds. In this study, it is shown that D. virilis has a higher resistance to oral infection of a species of filamentous fungi belonging to the genus Penicillium compared to D. melanogaster. In response to the fungal infection, a transcriptome profile of immune-related genes was considerably different between D. melanogaster and D. virilis: the genes encoding antifungal peptides, Drosomycin and Metchnikowin, were highly expressed in D. melanogaster whereas, the genes encoding Diptericin and Defensin were highly expressed in D. virilis. On the other hand, the immune-induced molecule (IM) genes showed contrary expression patterns between the two species: they were induced by the fungal infection in D. melanogaster but tended to be suppressed in D. virilis. Our transcriptome analysis also showed newly predicted immune-related genes in D. virilis. These results suggest that the innate immune system has been extensively differentiated during the evolution of these Drosophila species.